2003
DOI: 10.1002/sce.10071
|View full text |Cite
|
Sign up to set email alerts
|

Innovative science within and against a culture of “achievement”

Abstract: ABSTRACT:As science educators struggle to reform science education, we need a better understanding of the conundrums associated with the ways educators enact innovative science within and against the "academic," "rigorous," and "elite" sociohistorical constructions of science. I ethnographically investigated the meanings of an innovative, reform-based curriculum (Active Physics) in various micro (classroom) and macro (school and community) contexts. I conducted the study in a high school serving primarily uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 18 publications
3
80
0
1
Order By: Relevance
“…Every girl in this classroom reported to me that she was taking this class because ''it was the next one in the sequence for college-bound students'' or because ''it looks good on my transcript.'' These girls, within a culture of achievement in which it was a near certainty that they would attend college (Carlone, 2003b), accepted what Paul Willis (1977) called the dominant educational paradigm; they believed in teaching as a fair exchange, and they believed in the ways school defined success (i.e., via grades and college admission). In this sense, the Active Physics class was not supposed to be anything other than what it was-a way for them to get the credentials to put on their transcript so that they could gain access to an institute of higher education.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Every girl in this classroom reported to me that she was taking this class because ''it was the next one in the sequence for college-bound students'' or because ''it looks good on my transcript.'' These girls, within a culture of achievement in which it was a near certainty that they would attend college (Carlone, 2003b), accepted what Paul Willis (1977) called the dominant educational paradigm; they believed in teaching as a fair exchange, and they believed in the ways school defined success (i.e., via grades and college admission). In this sense, the Active Physics class was not supposed to be anything other than what it was-a way for them to get the credentials to put on their transcript so that they could gain access to an institute of higher education.…”
Section: Resultsmentioning
confidence: 88%
“…Elsewhere, I have reported the ways in which girls participated in ''Regular Physics'' (a class that used a traditional physics curriculum) at Sunnyglen High School (Carlone, 2003a) and the ways in which the meaning of the Active Physics at Sunnyglen High School curriculum got transformed as it traveled across space and time (Carlone, 2003b). The results of these ethnographic studies help make sense of the data I present here; thus, I will refer occasionally to the findings of these studies in my analysis.…”
Section: Ethnographic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is particularly true for physics, as this is probably the most tightly guarded of all the sciences (Angell, Guttersrud, Building physics in high school 5 Henriksen & Isnes, 2004). Carlone (2003) coined the term "prototypical" physics to describe the traditional practices and beliefs about science that have prevailed for decades. According to her, prototypical physics, envisioned as difficult, hierarchical, and objective, is still reproduced in everyday school practices, often masked as allegedly "reformed" physics.…”
Section: Content-centered and Progressive-learning Approachesmentioning
confidence: 99%
“…Concerning the substantial group of students who expressed that they needed to put more time and effort into studying than expected, it is not possible to state whether it was the students or the institutions that had unrealistic expectations of the effort to be invested by students. However, previous research has shown that upper-secondary school students generally perceive STEM studies (especially physics) as hard and demanding (Angell, Guttersrud, Henriksen, & Isnes, 2004;Carlone, 2003;Lyons & Quinn, 2010). In this perspective, it is noteworthy that so many of the students were surprised by the workload.…”
Section: Both Student Groups Were Surprised By the Effort And Motivatmentioning
confidence: 99%